2016
DOI: 10.1016/j.msea.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

In-situ investigation of stress-induced martensitic transformation in Ti–Nb binary alloys with low Young's modulus

Abstract: Microstructure evolution, mechanical behaviors of cold rolled Ti-Nb alloys with different Nb contents subjected to different heat treatments were investigated. Optical microstructure and phase compositions of Ti-Nb alloys were characterized using optical microscopy and X-ray diffractometre, while mechanical behaviors of Ti-Nb alloys were examined by using tension tests. Stress-induced martensitic transformation in a Ti-30at.%Nb binary alloy was in-situ explored by synchrotron-based high-energy X-ray diffractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 23 publications
4
18
0
1
Order By: Relevance
“…In fact, for 15 at.% Nb content, the hcp pure titanium is converted to an orthorhombic structure which is characterized by martensitic ′′ − Ti. The this martensitic phase at Nb concentrations around 15 at.% is supported by several other publications[47,48]. Furthermore, at 20 at.% of Nb content and beyond, the − Ti phase (bcc) can be stabilized at room temperature.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…In fact, for 15 at.% Nb content, the hcp pure titanium is converted to an orthorhombic structure which is characterized by martensitic ′′ − Ti. The this martensitic phase at Nb concentrations around 15 at.% is supported by several other publications[47,48]. Furthermore, at 20 at.% of Nb content and beyond, the − Ti phase (bcc) can be stabilized at room temperature.…”
supporting
confidence: 69%
“…At 15 at. % Nb, the orthorhombic martensite ′′ − Ti is formed with the lattice constants = 3.047, = 4.929, = 4.688 in close agreement with database values = 3.100, = 4.880, = 4.700[47,48]. The broad…”
supporting
confidence: 66%
“…The biocompatibility of niobium was also concerned to be higher than titanium [10]. Ti-Zr [11][12][13][14][15] and Ti-Nb systems [16][17][18][19][20][21] were already examined in several articles. It was reported that Ti-Zr alloys can improve biocompatibility properties of pure titanium, their mechanical strength and grind ability [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The thermal part is controlled by shot-range barriers such as the intersection of dislocations and the Peierls stress which is sensitive to temperature and strain rate. A higher strain rate can accelerate the multiplicity of dislocations, leading to the formation of dislocation tangles [53][54][55] which will retard the movement of dislocations. In addition, a higher temperature will supply dislocations with sufficient thermal energy to help them overcome dislocation tangles [33,41].…”
Section: Discussionmentioning
confidence: 99%
“…The origin of low Young's modulus in Ti-Nb-Ta-Zr alloys [51] and cold worked Ti-Nb-Ta-Zr-O alloys [52] have been studied and it is reported that "Young's modulus is lowest near the Martensite start temperature (M s )". Chang et al [53] investigated the effect of microstructures on the Young's modulus for Ti-Nb based alloys with different Nb contents and concluded that the Young's modulus depends directly on the chemical compositions of the alloy and its heat treatments.…”
Section: β Titanium Alloys For Biomedical Applicationsmentioning
confidence: 99%